2004
DOI: 10.1200/jco.2004.04.095
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Patient Preferences for Communication of Prognosis in the Metastatic Setting

Abstract: Most metastatic cancer patients want detailed prognostic information but prefer to negotiate the extent, format, and timing of the information they receive from their oncologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
387
3
7

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 441 publications
(405 citation statements)
references
References 47 publications
8
387
3
7
Order By: Relevance
“…Australian patients with metastatic cancer, especially those with a relatively better prognosis, showed a high need of detailed prognostic information. 9,33 In our study, in the metastatic groups prognosis was valued, both by the patient and the doctor, as even less important than in the early stage group. In fact, communicating prognosis to metastatic cancer patients is especially difficult, and requires considerable resources from both the patients and the doctors.…”
mentioning
confidence: 48%
See 1 more Smart Citation
“…Australian patients with metastatic cancer, especially those with a relatively better prognosis, showed a high need of detailed prognostic information. 9,33 In our study, in the metastatic groups prognosis was valued, both by the patient and the doctor, as even less important than in the early stage group. In fact, communicating prognosis to metastatic cancer patients is especially difficult, and requires considerable resources from both the patients and the doctors.…”
mentioning
confidence: 48%
“…1,[6][7][8][9][10][11][12][13][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] The patients' expectations also depend on the type of the disease, 15,20 or the type of the malignancy. 13,15,19,25 Most of the literature data on the attitude of breast cancer patients towards being informed, and participation in treatment decision come from Canada, 15,17,18,26,32 the US, 7,10,25,[27][28][29][30][31]34 Australia, 6,9,…”
Section: Discussionmentioning
confidence: 99%
“…Other research has shown that most patients want their oncologists to be willing to talk about death and dying [25,59] and cite emotional support as an important physician skill to help them cope when discussing the future [8]. Unfortunately, factors such as disease stage do not predict whether patients want to talk about end-of-life issues [41], so there is no reliable way to predict whether a given patient has concerns about death and dying.…”
Section: Discussionmentioning
confidence: 99%
“…Most cancer patients want these discussions [6] and value that their physician is comfortable talking about death and dying [7], though a significant minority of patients do not wish to discuss these issues [8]. Health professionals frequently avoid providing this information because they are uncertain of how much patients want to know or fear that patients and their families will lose hope [9].…”
Section: Introductionmentioning
confidence: 99%